Genetic Risk, Midlife Life's Simple 7, and Incident Dementia in the Atherosclerosis Risk in Communities Study. (12th July 2022) - Tin, Adrienne; Bressler, Jan; Simino, Jeannette; Sullivan, Kevin J.; Mei, Hao; Windham, B. Gwen; Griswold, Michael; Gottesman, Rebecca F.; Boerwinkle, Eric; Fornage, Myriam; Mosley, Thomas H.
Abstract : Background and Objectives: Higher scores in Life's Simple 7 (LS7), a metric for cardiovascular and brain health, have been associated with lower risk of dementia. It is uncertain whether this association holds among those with high genetic risk of dementia. Our objective is to evaluate the extent that LS7 may offset dementia risk across the range of genetic risk. Methods: Participants in the Atherosclerosis Risk in Communities (ARIC) Study were followed from 1987–1989 to 2019. We derived midlife LS7 scores and generated genetic risk scores (GRS) using genome-wide summary statistics of Alzheimer disease, which have been used to study the genetic risk for dementia. Incident dementia was ascertained based on the criteria of the National Institute on Aging–Alzheimer's Association workgroups and Diagnostic and Statistical Manual of Mental Disorders. The associations of the GRS and LS7 with incident dementia were evaluated using Cox regression. Results: This study included 8, 823 European American (EA) and 2, 738 African American (AA) participants (mean age at baseline 54 years). We observed 1, 603 cases of dementia among EA participants and 631 among AA participants (median follow-up 26.2 years). Higher GRS were associated with higher risk of dementia (EA, hazard ratio [HR] per SD 1.44, 95% CI 1.37, 1.51; AA, HR 1.26, 95% CI 1.16, 1.36). Among EA participants, higher LS7 scores were consistently associated with lower risk of dementia across quintiles of GRS, including the highest quintile (HR per point 0.91, 95% CI 0.87, 0.96). Among AA participants, the associations between LS7 and incident dementia within stratum of GRS had the same direction as among EA participants, although wide CIs and smaller sample sizes limited reliable inferences. Discussion: Across strata of GRS, higher midlife LS7 scores were associated with lower risk of dementia. Larger sample sizes from diverse populations are needed to obtain more reliable estimates of the effects of modifiable health factors on dementia risk within genetic risk strata in each ancestry group.